The Management of Student Moral Development in the Learning Process at Ihya' Ulumuddin Islamic Boarding School, Masbagik, East Lombok, West Nusa Tenggara, Indonesia - M. Sobry (International Journal of Science and Society, 2022)
The purpose of this study is to describe the management of students' moral development in the learning process at Ihya' Ulumuddin Islamic Boarding School, Masbagik, East Lombok, West Nusa Tenggara, Indonesia. This research uses a qualitative approach, with the type of case study. The subjects in this study were students and Islamic boarding school administrators. Data were collected using observation, interview and documentation techniques. The results showed that in the planning stage, Ihya' Ulumuddin Islamic boarding school from the beginning carried out strict moral development of students by requiring students to stay at the boarding school (not allowed to go home) without exception. In the actuating stage, the moral development of students is carried out by making classical moral books as a mandatory reference, such as Kitab Ta'lim Muta'alim, Kitab Akhlaq Lilbanin and Kitab Adab covering 50 manners in 50 situations. The controling stage of the students' moral development is enforced by giving sanctions in the event of an offence starting with a verbal warning to physical punishment that does not intend to hurt. The evaluation stage is carried out with three methods: direct supervision by all boarding school residents (ustadz and students), formal examinations, and the involvement of parents during school holidays. The moral development of students can be done by implementing a typical Islamic boarding school-based moral development management. This article demonstrates the uniqueness of Islamic boarding school-based moral development management that combines modern learning methods without having to abandon its classical salafy characteristics.